Effects of Flow Path Geometrical Parameters on Flow Characteristics and Hydraulic Performance of Drip Irrigation Emitters†. (19th September 2016) - Zhangzhong, Lili; Yang, Peiling; Li, Yunkai; Ren, Shumei
Abstract: In this paper, 13 fractal flow paths were designed and the effects of flow path geometric parameters on the internal flow characteristics and hydraulic performance explored. The results showed as the flow path width increased from 0.9 to 1.3 mm, the flow velocity followed from 1.83 to 2.43 m s −1 . There was significant difference in the turbulence intensity. The flow velocity (about 2.14 m s −1 ) and turbulence intensity distribution (5.6–48.1%) in flow paths with different depths were approximately the same. Different flow path lengths would obviously affect the values of the flow characteristics, while the distributions were similar. The length increased from 128 to 256 mm, the flow velocity decreased from 2.52 to 1.84 m s −1 and the maximum turbulence intensity dropped from 55.6 to 40.1%. As for hydraulic performance, the flow regime indexes were all about 0.49. The flow coefficient was obviously positively related to flow path width and depth, but very negatively correlated with flow path length and a prediction model of flow coefficient was constructed ( R 2  = 0.94). After comprehensive consideration, the optimized flow path width was about 1.0 mm, the length should be less than 224 mm, and a series of emitters with different flow rates could be developed by changing the depth. Copyright © 2016 John Wiley & Sons, Ltd.